Evolution of tenure and ownership of land in Cuba (Islas, 2023)
Introduction: The Cuban economy, and especially that of Santa Clara, during the 17th y 18th centuries, cannot be seen as unrelated to the process of land grants given with the beginning of Hispanic colonization.Methods: It has a theoretical-conceptual base supported by the theory and method of regional and local history. Based on this, they use the historical-logical, analytical-synthetic, inductive-deductive, analogical-comparative methods and the analysis of documents.Results: With the conquest of Cuban territory, Diego Velázquez applied the model of permanence in the place of the Spanish, who for this reason acquired the status of neighbor. The lands were granted in two different ways: lots and farmland. All land that belonged to the Indians, to the cities or to individuals is declared as public property or land of the King (realengas).Conclusions: Taking into account those analyzed and based on the Cuban case, four fundamental phases are defined for the formation of the communal property.
Keywords: land tenure; land ownership; Cuba; land grants